Chirality Induced Crystal Structural Difference in Metal Halide Composites. Issue 16 (27th May 2022) - Cai, Weidong; Qin, Jiajun; Pang, Tiqiang; Cai, Xinyi; Jia, Renxu; Gao, Feng
Abstract: Incorporating chiral organic compounds into metal halide frames is a common and useful method to introduce chirality in metal halide composites. The structures of resulting racemic and chiral composites are usually considered to be nearly identical owing to similar chemical bonding. In this work, by incorporating chiral MBABr (bromide methylbenzylamine) into an inorganic frame, a significant crystallization difference between the resulting racemic and chiral metal halide composites is observed, as confirmed by both structural and spectroscopic measurements. In addition, the structural transformation in the chiral composites can also be induced by moisture, ascribed to the asymmetric hydrogen bonding in chiral materials. These results provide new insights for the future synthesis of chiral materials and open up new possibilities to advance the materials functionalities. Abstract : Significant crystallization difference between resulting racemic and chiral lead‐free composites is observed by incorporating chiral MBABr (bromide methylbenzylamine) into the inorganic frame. In addition, in the chiral composites, structural transformation can be induced by moisture. Both effects are ascribed to the asymmetric hydrogen‐bonding of organic components in chiral materials.